Pengaruh Kepadatan Yang Berbeda Terhadap Kelulushidupan Dan Pertumbuhan Ikan Nila (Oreochromis niloticus) Pada Sistem Resirkulasi Dengan Filter Zeolit - Diansari, RR.Vanya Rhossitha; Arini, Endang; Elfitasari, Tita (Journal of Aquaculture Management and Technology, 2013)
Tilapia (Oreochromis niloticus) is a freshwater fish which have important economic value, easy to cultivate, good taste, inexpensive and have higher tolerance in different enviroment. Increased density until maximum carrying capacity will decrease growth of fish. The incrase in density will be followed by an increase in the amount of feed, wasted metabolism, oxygen consumption and can decrease water quality. Decline in water quality will result in slow growth and mortality. The purpose of this research was to explore the influence of different density and the best quantity for survival rate and growth of Tilapia (O. niloticus) in resirculation system with Zeolit filter and knowning the effetiveness of zeolite filter on resirculation system. This research used different density of Tilapia (O. niloticus ) size 4-6 cm. Eksperimental reserch conducted use. RAL (completely randomize design) with 3 treatmens and 3 replication. Treatment A (10 density of fish), Treatment B (15 density of fish) and Treatment C (20 density of fish). Data obtaired are to absolute long growth, rate of absolute specifics length, find ammonia levels, survival rate, feeding efficiency, and water quality parameters. The result showed that different density has significant effect towards the growth Tilapia but not for survival rate. The survival rate for each treatment was A = 86,67±5,77 %, B = 84,44±3,85 %, and C = 78,33±2,89 %. Rate of absolute specifics length in Tilapia at the highest treatment was A = 3,53±0,06 cm, and C = 2,57±0,06 cm. The average of specific growth rate on Tilapia was A treatment with highest of 2,45 0,07%/day, and the lowest is reatment C = 1,76 ±0,05%/day. The effectiveness of the treatment of a zeolite filter can word to the limit of the study. Compared with treatment B and C, which only reached day 20.